Enforced Electronic‐Donor‐Acceptor Complex Formation in Water for Photochemical Cross‐Coupling. (8th March 2023) - Tian, Ya‐Ming; Hofmann, Evamaria; Silva, Wagner; Pu, Xiang; Touraud, Didier; Gschwind, Ruth M.; Kunz, Werner; König, Burkhard
Abstract: The amino alcohol meglumine solubilizes organic compounds in water and enforces the formation of electron donor acceptor (EDA) complexes of haloarenes with indoles, anilines, anisoles or thiols, which are not observed in organic solvents. UV‐A photoinduced electron transfer within the EDA complexes induces the mesolytic cleavage of the halide ion and radical recombination of the arenes leading, after rearomatization and proton loss to C−C or C−S coupling products. Depending on the substitution pattern selective and unique cross‐couplings are observed. UV and NMR measurements reveal the importance of the assembly for the photoinduced reaction. Enforced EDA aggregate formation in water allows new activation modes for organic photochemical synthesis. Abstract : The sugar alcohol meglumine can solubilize organic compounds in water to synthetically useful levels, allowing the formation of enforced electron donor acceptor (EDA) complexes in water. These EDA complexes offer a new activation for light driven C−C and C−S cross‐coupling chemistry without sensitizers.